2020
DOI: 10.1186/s12911-020-01177-z
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of data access and use procedures in clinical data warehouses. A systematic review of literature and publicly available policies

Abstract: Background: The promises of improved health care and health research through data-intensive applications rely on a growing amount of health data. At the core of large-scale data integration efforts, clinical data warehouses (CDW) are also responsible for data governance, managing data access and (re)use. As the complexity of the data flow increases, greater transparency and standardization of criteria and procedures are required in order to maintain objective oversight and control. Therefore, the development o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
0
21
0
1
Order By: Relevance
“…Accountability also demands that an organisation or a research body clearly identifies and discloses who is accountable for the management of data [A 43 ]. Some of the sources present accountability in terms of data use [A 44 46 , 48 ] while some highlight accountability in terms of organisational accountability [A 43 , 46 ]. Some sources also reference how the principle is reflected in data laws, for example, the GDPR’s principle of accountability of data controllers moves the onus of proof onto data controllers, thereby reducing the need for data subjects to demonstrate causation in many contexts [A 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accountability also demands that an organisation or a research body clearly identifies and discloses who is accountable for the management of data [A 43 ]. Some of the sources present accountability in terms of data use [A 44 46 , 48 ] while some highlight accountability in terms of organisational accountability [A 43 , 46 ]. Some sources also reference how the principle is reflected in data laws, for example, the GDPR’s principle of accountability of data controllers moves the onus of proof onto data controllers, thereby reducing the need for data subjects to demonstrate causation in many contexts [A 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, accountability provides mechanisms for communicating health relevant information to data subjects [A 45 ]. Sources also agree that accountability can increase public trust in situations such as data reuse [A 48 , 49 ]. One author pointed out that it is necessary as a good governance practice to establish an accountable decision-making body that can provide assurances that data are being used and linked appropriately and responsibly [A 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Data governance practices will necessarily vary by institution. Our governance approach has commonalities with the spectrum of criteria and procedures described in Pavlenko et al 11 including requirements for human subjects protection training, IRB approval, and data sharing agreements, and attention to patients’ perspectives and institutional reputation when reviewing requests. Notably, however, the spectrum in Pavlenko does not include an explicit focus on whether a request is limited to the minimum necessary data.…”
Section: Discussionmentioning
confidence: 99%
“… 10 A recent systematic review on data access and use in clinical data warehouses found a lack of in-depth information on data governance and criteria used for reviewing requests. 11 This article seeks to fill that void by describing the governance approach at the University of North Carolina at Chapel Hill for research uses of the Carolina Data Warehouse for Health (CDW-H), the central repository for electronic health record (EHR) data for UNC Health.…”
Section: Introductionmentioning
confidence: 99%
“…As the complexity of the data flow increases, greater transparency and standardization of criteria and procedures are required to maintain objective oversight and control. The development of practice-oriented and evidence-based policies in this field is crucial [ 26 , 27 ]. On this point, it is interesting to note the recent initiative of the National Commission for Data Protection and Liberties in France (CNIL).…”
mentioning
confidence: 99%